Strategic Planning and Business Sustainability of SMEs in Kigezi Sub-Region Uganda - Turtasingura John Bosco; Agaba Moses; Kabagabe Jesse David (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2023)
This study looked at how strategic planning affected business sustainability of small and medium-sized businesses in Uganda. A Kigezi sub-regional case. Utilizing a correctional sectional study design, the investigation was conducted. The study's use of both quantitative and qualitative approaches allowed it to evaluate the relationship between the factors it was examining. A sample of 105 respondents was selected using simple random selection and purposive sampling techniques. The quantitative and qualitative data from the respondents were analyzed using SPSS Version 23.0 and theme analysis, respectively. Tables providing quantitative results in the form of descriptive statistics, correlations, and regressions were presented based on the study's goals. The study found a significant association between strategic planning and the long-term viability of SMEs' businesses (r =.789, P.01). The research's findings and analyses indicate a strong relationship between strategic planning and SMEs' ability to remain competitive in the Kigezi sub-region. According to the study, the majority of respondents said that long-term success for SMEs was strongly impacted by strategic planning. According to the study, SMEs should focus on strategic planning for business longevity if they want to successfully continue their businesses.